In search of recognition: youth participation In 'traditional' dancing In Nyanga, Cape Town - Tanino, Rise (Department of Psychology, 2026)
This ethnographic study examines the experiences of young Black South Africans in seeking recognition through engagement in ‘traditional' dance. Based on six months of ethnographic research with a group of young ‘traditional' dancers in Nyanga township, Cape Town, it investigates the creative use of dance and strategies deployed by a group of young people to gain recognition as humans and as accomplished social adults. In a context in which young people must compete to fit across ever-shifting expectations of accomplishment, ‘traditional' dancing offers them a creative space to activate collective agency, negotiate visibility, being human and participate in community. Building on research about youth, dance, and recognition, I argue that youth in Nyanga employ economic, artistic, and organizational strategies in their ‘traditional' dancing to gain recognition. These strategies enable them to accumulate resources to be acknowledged in the consumerist and post- apartheid context, to quip them with outlet to express their emotions, and having stake and space in the community, allowing them to gain dignity as humans and as young people.